Case studies in gerontological nursing for the advanced practice nurse - Kazer, Meredith Wallace ;Neal-Boylan, Leslie (Hoboken, New Jersey : John Wiley & Son, Inc., 2012)
As the fastest growing population sector worldwide, older adults are seen in almost every care setting in which clinicians practice. Developed as a resource for advanced practice nurses in any setting, Case Studies in Gerontological Nursing for the Advanced Practice Nurse presents readers with a range of both typical and atypical cases from real clinical scenarios. The book is organized into six units covering cases related to ageism, common health challenges, health promotion, environments of care, cognitive and psychological issues, and issues relating to aging and independence.
Section 1: The Aging Population -- Case 1.1 Recipe for Successful Aging -- Case 1.2 Cultural Competence Is a Journey -- Case 1.3 The Ugly Face of Ageism -- Case 1.4 If Only We Had National Health Insurance -- Section 2: Common Health Challenges of Aging -- Case 2.1 The Heart of It All -- Case 2.2 I Have This Thing on My Skin -- Case 2.3 Why Is My Mother Wearing a Diaper? -- Case 2.4 My Aching Back -- Case 2.5 More Than Just Constipation -- Case 2.6 Are You in the Hospital Again? Case 2.7 It Hurts When I PeeCase 2.8 The History Reveals All -- Case 2.9 Kneedless Pain -- Case 2.10 Life after a Right CVA -- Case 2.11 It Takes My Breath Away -- Case 2.12 What's Shaking? -- Case 2.13 Too Much to Manage -- Case 2.14 Them Bones, Them Bones -- Section 3: Health Promotion -- Case 3.1 Never Too Old to Quit -- Case 3.2 Protection by Prevention -- Case 3.3 Is Being Careful Enough? -- Case 3.4 Sick and Tired of Being Sick and Tired -- Case 3.5 To Screen or Not to Screen -- Section 4: Environments of Care -- Case 4.1 Who Says I Can't Go Home -- Case 4.2 Regressing in Rehab -- Case 4.3 There's No Place Like Home. Case 4.4 Caring for the CaregiverCase 4.5 Transitions -- Case 4.6 Shifting the Focus of Care -- Case 4.7 Without a Home -- Case 4.8 A Place Called Home -- Case 4.9 Aging in Place -- Section 5: Cognitive and Psychological Issues in Aging -- Case 5.1 The Diabolical Ds -- Case 5.2 What a Difference a Day Makes -- Case 5.3 I Don't Feel Good -- Case 5.4 Understanding Distress -- Section 6: Issues of Aging and Independence -- Case 6.1 Too Much of a Good Thing -- Case 6.2 Driving in My Car -- Case 6.3 Sex Does Not Stop with Seniority -- Case 6.4 Hidden Pathology -- Case 6.5 Taking Control of the Pain. Case 6.6 The Road toward End-of-Life Decision Making: Who Has the Right of Way?Index
Includes bibliographical references and index.
Keywords: GERIATRIC NURSING -- CASE STUDIES